Boundary layer characteristics associated with sea breeze circulation over Cochin (MAUSAM, 2007)
Features of sea and land breezes, surface fluxes and drag coefficient over Cochin are studied using more than 300 daily observations of air temperature, wind speed and direction data. The duration and intensity of sea breeze circulation vary with the rain or cloud as it reduces the differential heating. Onset of sea breeze is early in summer season for the near equatorial station compared to winter season. Cessation is almost same for all seasons and is around 1900 hours. The sea breeze circulation is almost westerly and land breeze circulation is almost easterly in all the seasons. It is found that in most of the cases, the temperature and wind speed decreases at the time of onset of sea breeze and turning of wind direction with height becomes counter clockwise (backing) during the transition period from land breeze to sea breeze. In all seasons, the momentum flux is directed downward. High values of momentum flux were found during the presence of sea breeze in pre-monsoon season. Average sensible heat flux is directed upward during the entire period and during nighttime it is almost zero in the winter and monsoon seasons. The intensity of momentum flux decreases during onset and cessation of sea breeze for all the cases. The cold air advection associated with the sea breeze results in the decrease of sensible heat flux at the time of onset of sea breeze. Averaged surface momentum and sensible flux patterns resemble closely to the instantaneous pattern for all the seasons. Generally, sea breeze is stronger than land breeze in all the seasons. Accordingly, the drag coefficient power relationship with wind is different for sea breeze and land breeze circulations.Key words – Sea breeze circulation, Monsoon boundary layer, Surface fluxes, Drag coefficient, Diurnal variation.